Trends and treatment outcomes of drug resistant tuberculosis in Limpopo Province, South Africa (2011–2019): A Retrospective Study - Kabelo Gabriel Kaapu; Ivy Rukasha (PLoS ONE, 2025)
Background Drug-resistant tuberculosis (DR-TB) continues to threaten TB control efforts in South Africa, particularly in resource-limited provinces such as Limpopo. This study evaluated trends in DR-TB and evaluated treatment outcomes and predictors of unfavorable outcomes from 2011 to 2019. Methods We conducted a retrospective cross-sectional study using data from 3,528 patients with DR-TB recorded in the Limpopo electronic registry (EDRWeb.net). Descriptive statistics characterized the demographics of the patients and the types of resistance. The associations between variables and outcomes were tested using chi-square analysis and binary logistic regression identified independent predictors of unfavorable treatment outcomes. The study period was stratified into pre-bedaquiline (BDQ) (2011–2015) and post-BDQ (2016–2019) eras to assess the impact of treatment. Results Rifampicin-resistant TB (RR-TB) (61.7%) and multidrug-resistant TB (MDR-TB) (32.5%) were the most common. Overall, the success of the treatment was 59.0%, increasing from 54.1% in the pre-BDQ era to 65.3% after BDQ. XDR-TB had the lowest success rate (31.3%). In multivariate analysis, male sex (aOR = 1.12; 95% CI: 1.00–1.27), HIV positivity (aOR = 1.28; 95% CI: 1.11–1.47), age ≥ 35 years (aOR = 2.01; 95% CI: 1.08–3.76), and XDR-TB (aOR = 3.05; 95% CI: 1.65–5.65) were independently associated with unfavorable outcome. Conclusion Treatment outcomes for DR-TB in Limpopo improved following the introduction of BDQ and shorter all-oral regimens but remain suboptimal, particularly among XDR-TB and HIV co-infected patients. Strengthening TB/HIV integration, expanding access to new drug regimens, and enhancing early diagnosis are essential to improve outcomes in rural high-burden settings.